What and Where is God? A Human Answer to the Deep Religious Cry of the Modern Soul - Swain, Richard La Rue, 1860- (Salt Lake City, UT : Project Gutenberg, 2011)
"What and Where is God? A Human Answer to the Deep Religious Cry of the Modern Soul" by Richard LaRue Swain, Ph.D. is a philosophical and theological exploration written in the early 20th century. This work addresses profound questions concerning the existence and nature of God amidst the context of modern understanding and skepticism. The author seeks to provide a coherent conception of God, man, and the universe, bridging the gap between traditional religious beliefs and contemporary scientific insights. The beginning of this text introduces readers to the personal struggles of individuals grappling with the concept of God in an era marked by doubt and changing values. It opens with the poignant account of a minister's wife who expresses her disconnection from the idea of God, reflecting a broader crisis of faith faced by many. Through a series of questions and contemplative reflections, Swain emphasizes the necessity of refining our understanding of God in a way that resonates with modern knowledge and experience. He critiques outdated perceptions of God while laying the groundwork for a more relatable and dynamic conception of the Divine, aiming to address the deep religious cry inherent in contemporary society. (This is an automatically generated summary.)
Release date is 2011-07-01
E-text prepared by Charlene Taylor, Marilynda Fraser-Cunliffe, and the Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: Christianity; God (Christianity)